Inhibition of Neutrophil Secretion Upon Adhesion as a Basis for the Anti-Inflammatory Effect of the Tricyclic Antidepressant Imipramine - Galkina, Svetlana I.; Golenkina, Ekaterina A.; Fedorova, Natalia V.; Ksenofontov, Alexander L.; Serebryakova, Marina V.; Arifulin, Evgenii A.; Stadnichuk, Vladimir I.; Baratova, Ludmila A.; Sud’ina, Galina F. (Frontiers in Pharmacology, 2021)
Recent studies demonstrate the involvement of inflammatory processes in the development of depression and the anti-inflammatory effects of antidepressants. Infiltration and adhesion of neutrophils to nerve tissues and their aggressive secretion are considered as possible causes of inflammatory processes in depression. We studied the effect of the antidepressant imipramine on the adhesion and accompanied secretion of neutrophils under control conditions and in the presence of lipopolysaccharides (LPS). As a model of integrin-dependent neutrophil infiltration into tissues, we used integrin-dependent adhesion of neutrophils to the fibronectin-coated substrate. We studied the effect of the antidepressant imipramine on the adhesion of neutrophils to fibronectin and the accompanying production of reactive oxygen species (ROS) and the secretion of proteins and free amino acids under control conditions and in the presence of lipopolysaccharides (LPS). Our data showed that imipramine Imipramine inhibiteds neutrophil adhesion and concomitant secretion of proteins, including matrix metalloproteinase 9 (MMP-9) and neutrophil gelatinase-associated lipocalin (NGAL), which modify the extracellular matrix and basement membranes required for cell migration. Imipramine also significantly and selectively blocked the release of the free amino acid hydroxylysine, a product of lysyl hydroxylase, an enzyme that affects the organization of the extracellular matrix by modifying collagen lysine residues. In contrast, imipramine enhanced the release of ROS by neutrophils during adhesion to fibronectin and stimulated apoptosis. The anti-inflammatory effect of imipramine may be associated with the suppression of neutrophil infiltration and their adhesion to nerve tissues by inhibiting the secretion of neutrophils, which provides these processes.